Electrodeposition of porous metal-organic frameworks for efficient charge storage - Deepa B. Bailmare; Boris V. Malozyomov; Abhay D. Deshmukh (Communications Chemistry, 2024)
Abstract Efficient charge storage is a key requirement for a range of applications, including energy storage devices and catalysis. Metal-organic frameworks are potential materials for efficient charge storage due to their self-supported three-dimensional design. MOFs are high surface area materials made up of coordination of appropriate amounts of metal ions and organic linkers, hence used in various applications. Yet, creating an effective MOF nanostructure with reduced random crystal formation continues to be a difficult task. The energy efficiency and electrochemical yield of bulk electrodes are improved in this study by demonstrating an effective technique for growing MOFs over a conducting substrate utilizing electrodeposition. An exceptionally stable asymmetric supercapacitor is created when activated carbon cloth is combined with the resulting MOF structure that was directly synthesized via an electrochemical method resulting in 97% stability over 5k cycles which is higher than conventional processes. High performance in supercapacitors is ensured by this practical approach for producing MOF electrodes, making it a suitable structure for effective charge storage.